2018
DOI: 10.1002/cite.201800098
|View full text |Cite
|
Sign up to set email alerts
|

Modellierung und Simulation von Vollmantelzentrifugen als ein Aspekt der voranschreitenden Digitalisierung in der Fest/Flüssig‐Trennung

Abstract: Im Zuge der Initiative Industrie 4.0 erhöht sich der Digitalisierungsgrad auch in der Prozessindustrie. Eine enge Verknüpfung von Analyseverfahren und dynamischer Prozessmodelle erlaubt die Optimierung der Prozesskontrolle und Steuerung auch in der industriellen Trenntechnik. Zu diesem Zweck müssen mathematische Modelle zur Beschreibung der Prozessebene in Echtzeit bekannt sein. Im Bereich der Fest/Flüssig‐Trennung erzwingt die voranschreitende Digitalisierung die Entwicklung von numerischen Methoden und von S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 41 publications
(53 reference statements)
0
5
0
Order By: Relevance
“…For the other materials studied, where desaturation by applying gas pressure difference is not possible and, thus, the residual moisture remains constant after cake formation, vibration compaction has a clear advantage, as shown by the significant reduction in porosity, further displacing liquid from the cake. The use of steady shear with simultaneous squeezing to compact ground calcium carbonate products was investigated by Hammerich et al [31,32] in a lab-scale press shear cell. Steady shear at a shear rate of 1.5 mm/min at a normal pressure up to 60 kPa results in an average porosity of 0.4 for a ground calcium carbonate product with a mean particle size (x 50,3 ) of about 6 µm.…”
Section: Comparison Of the Compaction Or Deliquoring Results By Oscil...mentioning
confidence: 99%
See 1 more Smart Citation
“…For the other materials studied, where desaturation by applying gas pressure difference is not possible and, thus, the residual moisture remains constant after cake formation, vibration compaction has a clear advantage, as shown by the significant reduction in porosity, further displacing liquid from the cake. The use of steady shear with simultaneous squeezing to compact ground calcium carbonate products was investigated by Hammerich et al [31,32] in a lab-scale press shear cell. Steady shear at a shear rate of 1.5 mm/min at a normal pressure up to 60 kPa results in an average porosity of 0.4 for a ground calcium carbonate product with a mean particle size (x 50,3 ) of about 6 µm.…”
Section: Comparison Of the Compaction Or Deliquoring Results By Oscil...mentioning
confidence: 99%
“…The benefit of steady shear for filter cake deliquoring also depends, in this case, on the nature of the slurry. In lab-scale press shear cells, several authors have observed positive effects of shear for cake deliqouring to various degrees of kaolin [28,29], mica [28], talc [29], titanium dioxide [30], and limestone [31,32]. However, for activated sludge, as a highly compressible material, Vaxelaire [29] showed that shear did not contribute to any additional deliquoring due to the high cake resistance and the lack of rigidity of the particles for rearrangement.…”
Section: Introductionmentioning
confidence: 99%
“…The basis of this approach was the description of the sedimentation and consolidation behavior via the flux density function analogous to Bürger and Concha [27]. Solid particles and fluid are approached as a single mixed phase which is shown in Figure 1 similar to Hammerich [32]. [32]: The two-phase system consisting of particles and liquid has been described as an incompressible mixed phase.…”
Section: General Approachmentioning
confidence: 99%
“…Figure 1. Schematic representation of the transport equation of the dispersed phase and its influence on the flow conditions based on Hammerich[32]: The two-phase system consisting of particles and liquid has been described as an incompressible mixed phase. The solids volume fraction allows the division of the simulation geometry into two different regions, slurry and sediment.…”
mentioning
confidence: 99%
“…13,14 This process accelerates the settling rate and ratio of soluble or insoluble substrates to separate different contents with different settling coefficients and buoyancy densities from a liquid. [15][16][17] High-speed centrifugation plays a vital role in laboratory scale separation, [18][19][20] but it has some limitations, including complex processes, large equipment investment, and high energy consumption, during industrial scale production. [21][22][23][24] So far, many new and efficient methods have been developed for microbial cell separation and recycling to achieve simple and economical fermentation for commercial use.…”
Section: Introductionmentioning
confidence: 99%